Interview with Jaime Oliver La Rosa (1979) by Aurelio Tello - Tello Malpartida, Aurelio (2024)
Jaime Oliver La Rosa came to music out of childhood curiosity and made it a refuge after the death of his mother. Although he did not see a viable career in Peru, a scholarship in California allowed him to pursue computer music, leading to a post-doc at Columbia and teaching at NYU. He opted for electronic music due to the inaccessibility of instrumental formations in Peru and the anachronistic nature of the European repertoire. Influenced by artists such as Berio, Xenakis and Oliveros, and by Peruvians such as Bolaños and Valcárcel, he explored live electronic music and collaborated with visual artists. He created instruments such as MANO and the Silent Drum to reintegrate the body and gesture into electronic music. He reflects on identity in his music, influenced by its context without explicitly seeking a "Peruvianness." He highlights the importance of artificial intelligence in musical creation and the relationship between composition and popular music or sound art. He values ??the contributions of previous Peruvian electronic musicians and believes that the barriers between musical genres are blurring, which is interesting for the future of electronic music.